Not so healthy, not so comfortable: Health anxiety in people living with HIV and its relationship to quality of life and psychosocial functioning - Yildiz, Nazim; Nayki, Utku; Mete, Bilgul; Fadiloglu, Kubra; Nergiz, Ali Ihsan; Kocabasoglu, Nese (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2021)
Background: People living with Human Immundeficiency Virus (PLWH) are often inclined to attribute their bodily sensations to HIV (Human Immundeficiency Virus) without considering those as malign or benign. Thus, it’s thought that health anxiety may be high in these individuals. We aim to determine the levels of health anxiety in PLWH and its relation with quality of life and psychosocial functioning. Methods: PLWH, Type-I diabetes mellitus (DM) patients and healthy individuals were included. CD4+T lymphocytes counts and HbA1C values were obtained. Sociodemographic data form, General Health Questionnaire (GHQ), Health Anxiety Inventory (HAI), Social Adaptation Self Evaluation Scale (SASS), SF-36 QoL Form, Beck Depression and Beck Anxiety Scale (BDI, BAI) were applied to subjects. Comparisons and regression analyzes were made. Results: Total of 228 subjects were included in study. Health anxiety levels in HIV group were higher than control groups. SASS scores were not different than in Type-I DM group’s scores, whereas the BDI, BAI, and GHQ scores were worse in the HIV group than in the other groups. There was a significant difference in the QoL between healthy controls and HIV group. CD4+ T lymphocyte count had the highest explanotory power for the psychometric scores. Conclusions: PLWH have higher health anxiety than controls. Psychosocial functioning and QoL are impaired in people with high health anxiety levels. CD4+ T lymphocyte count is strongest explanatory factor on almost every subscale. The disease itself seems to disrupt the quality of life and psychosocial harmony beyond the psychological picture it creates.